PENGARUH PELATIHAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA HOTEL GARUDA PLAZA DI KOTA MEDAN - Anggraini, Ayu (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
This study is based on the idea that job training is one way to improve employee productivity which will further improve the company’s productivity. The purpose of this study was to investigate and analyze whether the job training effect on employee productivity at Garuda Plaza Hotel Medan. This research was conducted at Garuda Plaza Hotel Medan. The approach used in this study is a quantitative approach with descriptive research. The results showed that job training effect positive and significant on labor productivity at Garuda Plaza Hotel Medan. From the t test calculation results obtained tcount of 14.185, meaning tcount > ttable (14.185 > 1.992). From the data processing coefficient of determination (R2) obtained R2 values of 0,726 this means job training variables are able to explain the variable productivity of employees amounted to 72,6 % while the remaining 27,4 % variable labor productivity can be explained by other variables outside variables used in this study.